A neurophysiologically‐based analysis of lightness and brightness perception. Issue 4 (11th May 2015) - Seim, Thorstein; Valberg, Arne
Abstract: Psychophysical, achromatic luminance threshold, and scaling data have been analyzed and found to follow from nonlinear, hyperbolic responses of retinal cones. For short (0.1 s) stimulus duration, a stable state of visual adaptation could explain the threshold response, but for longer durations a change of adaptation had to be considered. This resulted in a contrast sensitivity that increased when the stimulus duration increased and became constant for higher test field luminances. Threshold and scaling data can thus be traced back to cone‐specific responses over a much larger range of stimulus intensity than has been anticipated earlier. The experimental results, including those for lightness and brightness scaling, have been compared with the CIELAB and the CIEDE2000 color formulas. The idea of combining cone responses with adaptive changes to describe luminance responses resulted in a common cone‐based response formula for describing both luminance thresholds and scaling data. Adaptive changes explain the reason why both Weber–Fechner and Stevens' laws are valid. © 2015 Wiley Periodicals, Inc. Col Res Appl, 41, 339–351, 2016